World Cup for Whom? Goals of Resistance Movements to 2014 World Cup - Yamim, Amanda Pruski; Bossle, Marília Bonzanini; Pojo, Sabrina da Rosa; Rossi, Carlos Alberto Vargas (Revista de Administração da UFSM, 2016)
Consumer relations that permeate a sportive mega-event are large and should be considered from the consumption of the games, as well as any modification of contextual consumption directly or indirectly caused. In a large extent, it is known that the World Cup impacts international, national and local consumption, even reaching the public not adept to soccer. However, in recent years can be observed in the country a counter consumption chain. Considering that, this study aims to understand the central objectives related to resistance movements to the 2014 World Cup. To achieve the proposed objectives, this research is conducted with a qualitative approach through in-depth interviews and secondary data analysis. The importance of this study is related to the context in Brazil lived in 2014 and mainly in the host cities. We conclude that the resistance is towards power relations existing in the market and not to the World Cup event, which is no longer associated with the symbolic aspect of soccer and is seen as a precondition and opportunity for greater dialogue among consumer, company and government.